2019
DOI: 10.1002/jssc.201900379
|View full text |Cite
|
Sign up to set email alerts
|

Rapid screening and purification of potential alkaloid neuraminidase inhibitors from Toddalia asiatica (Linn.) Lam. roots via ultrafiltration liquid chromatography combined with stepwise flow rate counter‐current chromatography

Abstract: Toddalia asiatica (Linn.) Lam. is a medical plant traditionally used to treat coughs, fevers, and various diseases. Alkaloids are the main active ingredients in Toddalia asiatica (Linn.) Lam., but traditional methods for screening and separation are complex and labor‐intensive. In this work, an efficient strategy was developed to rapidly screen, identify, and separate neuraminidase inhibitors from Toddalia asiatica (Linn.) Lam. Ultrafiltration, high performance liquid chromatography, and time‐of‐flight mass sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Compared with traditional column chromatography, HSCCC has the advantages of large sample loading, high recovery, high efficiency, and easy scale‐up potential [5,6]. In addition, the various modes available to date, such as normal phase [7,8], reverse phase [9,10], gradient mode [11,12], recycling mode [13,14], pH Zone refining [15,16], extrusion [17], and dual‐mode [18], have made it widely used in the isolation and purification of active components from natural products. However, it is sometimes not easy to find a suitable solvent system, especially for compounds with a similar polarity, to perform an ideal separation.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with traditional column chromatography, HSCCC has the advantages of large sample loading, high recovery, high efficiency, and easy scale‐up potential [5,6]. In addition, the various modes available to date, such as normal phase [7,8], reverse phase [9,10], gradient mode [11,12], recycling mode [13,14], pH Zone refining [15,16], extrusion [17], and dual‐mode [18], have made it widely used in the isolation and purification of active components from natural products. However, it is sometimes not easy to find a suitable solvent system, especially for compounds with a similar polarity, to perform an ideal separation.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the continuous researches reported at home and abroad, scholars have found that alkaloids in T. asiatica played an important role in anti-inflammatory, analgesic, and anti-tumor effects ( Hao et al, 2004 , Hu et al, 2014 ). A rapid method using ultrafiltration liquid chromatography combined with stepwise flow rate counter-current chromatography was developed to screen and purify alkaloid that could be used as neuraminidase inhibitors ( Cao et al, 2019 ). Quinoline alkaloids in the plant are primarily N-methylflindersine, toddacoumalone, skimmianine, integriquinolone, dictamnine, hannine, and oxyterihannine, etc.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…High-speed counter-current chromatography (HSCCC) using the n -hexane/ethyl acetate/methanol/water (10:10:11:9, v / v ) solvent system is reported for the separation of isopimpinellin, pimpinellin, and phellopterin from T. asiatica [ 21 ]. Recently, in a previous study conducted by our group, the n -hexane/ethyl acetate/methanol/water (5:5:3:7, v / v ) biphasic solvent system was successfully used to separate toddalolactone, leptodactylone, haplopine, skimmianine, and 5-methoxydictamnine from T. asiatica [ 22 ].…”
Section: Introductionmentioning
confidence: 99%